Reactive power tracking in a power transmission networks / Zulailah Zakaria - Zakaria, Zulailah (2007)
This thesis presents reactive power tracking in a power transmission networks. This proposes a comprehensive power tracking methodology to assess the reactive power performance in network-wide applications. The tracking algorithm is based on electric circuit's principles using IEEE 14-bus power transmission as the test specimen. It is originated by the power flow solution of a network. In this study emphasis is place on the dominion loss of the transmission lines in order to determine the allocating charges for the use of line.